2021
DOI: 10.3390/cancers13061332
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility Study of Hypofractionated Radiotherapy with Regional Hyperthermia in Soft Tissue Sarcomas

Abstract: Introduction: Management of marginally resectable or unresectable soft tissue sarcomas (STS) in patients who are not candidates for neoadjuvant chemotherapy due to chemoresistant pathology or contraindications remains a challenge. Therefore, in these indications, we aimed to investigate a feasibility of 10x 3.25 Gy radiotherapy combined with regional hyperthermia (HT) that could be followed by surgery or 4x4 Gy radiotherapy with HT. Materials and methods: We recruited patients with locally advanced marginally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Achieving durable LC in unresected STS with RT has been limited by its radioresistant nature, 4 , 5 , 6 , 7 , 8 with photon-based 5-year LC of 28 to 73%. 31 Many attempts have been made to improve the LC for unresectable STS treated with RT, including concurrent systemic therapy, 32 heavy ion therapy, 33 combined hyperthermia, 34 and hypofractionation. 35 However, our study demonstrated impressive outcomes using our novel HARD photon-based regimen, with no instances of local or regional progression observed in this historically radioresistant cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Achieving durable LC in unresected STS with RT has been limited by its radioresistant nature, 4 , 5 , 6 , 7 , 8 with photon-based 5-year LC of 28 to 73%. 31 Many attempts have been made to improve the LC for unresectable STS treated with RT, including concurrent systemic therapy, 32 heavy ion therapy, 33 combined hyperthermia, 34 and hypofractionation. 35 However, our study demonstrated impressive outcomes using our novel HARD photon-based regimen, with no instances of local or regional progression observed in this historically radioresistant cohort.…”
Section: Discussionmentioning
confidence: 99%
“…If proven effective, this technique could merge with the broader front of the management of STS including marginally resectable and unresectable, in which novel approaches of combining various fractionation RT schemes with other treatment modalities including hyperthermia and chemotherapy have been actively proposed and investigated. 90 , 91 …”
Section: Discussionmentioning
confidence: 99%
“…Currently hypofractionated preoperative RT may be advised [87,88]. Referral to a sarcoma center for hypofractionated radiotherapy with hyperthermia may be considered in patients with marginally resectable or unresectable ES and in patients who are not eligible for chemotherapy [89]. Adjuvant radiation therapy is recommended in cases with positive margins (R1/R2 resections).…”
Section: Discussionmentioning
confidence: 99%